Cardiac markers in children and adolescents at the onset of type 1 diabetes mellitus - Sara Musterer; Mandy Vogel; Wieland Kiess; Sandy Richter; Heike Bartelt; Christof Meigen; Uta Ceglarek; Anja Willenberg; Ronald Biemann; Thomas Kapellen; Alexandra Kiess (PLoS ONE, 2026)
Background The incidence of type 1 diabetes mellitus (T1DM) in children and adolescents is rising, and both micro- and macrovascular complications pose significant health risks. For ketoacidosis or fluctuations in blood glucose, myocardial injury may occur and lead to severe complications. Cardiac markers such as high-sensitivity troponin T and N-terminal pro-b-type natriuretic peptide (NT-proBNP) are used to detect cardiovascular damage in adults but have been explored less in pediatric populations with T1DM. Objective We aimed to investigate the relationships between high-sensitivity troponin T and NT-proBNP levels at T1DM onset and their associations with metabolic markers (Hemoglobin A1c, pH, and glucose) to identify potential early markers of myocardial damage in children with diabetes. Methods 306 children and adolescents with newly diagnosed T1DM were enrolled from our hospital, while a matched control group of 1,259 healthy children was drawn from the LIFE Child study. Blood samples were analyzed for high-sensitivity troponin T and NT-proBNP concentrations. Descriptive statistics and censored regression models were used to assess associations between biomarkers and metabolic parameters. Results Children with recent T1DM had significantly higher high-sensitivity troponin T levels and lower NT-proBNP levels than the control group. High-sensitivity troponin T levels were positively correlated with Hemoglobin A1c in the T1DM group, while NT-proBNP levels were negatively associated with the pH value. For blood glucose levels, a significant correlation was found between blood glucose and high-sensitivity troponin T, but no association was observed with NT-proBNP. There was a significant association between weight change during hospitalization and high-sensitivity troponin T in female patients. Conclusion Elevated high-sensitivity troponin T and reduced NT-proBNP levels at T1DM onset suggest early myocardial stress in affected children. These cardiac markers, in conjunction with metabolic parameters, could serve as potential early indicators of cardiovascular risk in this population.